Low anterior resection syndrome in a Scandinavian population of patients with rectal cancer: a longitudinal follow‐up within the QoLiRECT study. (22nd May 2020) - Sandberg, S.; Asplund, D.; Bisgaard, T.; Bock, D.; González, E.; Karlsson, L.; Matthiessen, P.; Ohlsson, B.; Park, J.; Rosenberg, J.; Skullman, S.; Sörensson, M.; et al.
Abstract: Aim: Low anterior resection syndrome (LARS) is common after low anterior resection. Our aim was to evaluate the prevalence and 'bother' (subjective, symptom‐associated distress) of major LARS after 1 and 2 years, identify possible risk factors and relate the bowel function to a reference population. Method: The QoLiRECT (Quality of Life in RECTal cancer) study is a Scandinavian prospective multicentre study including 1248 patients with rectal cancer, of whom 552 had an anterior resection. Patient questionnaires were distributed at diagnosis and after 1, 2 and 5 years. Data from the baseline and at 1‐ and 2‐year follow‐up were included in this study. Results: The LARS score was calculated for 309 patients at 1 year and 334 patients at 2 years. Prevalence was assessed by a generalized linear mixed effects model. Major LARS was found in 63% at 1 year and 56% at 2 years. Bother was evident in 55% at 1 year, decreasing to 46% at 2 years. Major LARS was most common among younger women (69%). Among younger patients, only marginal improvement was seen over time (63–59%), for older patients there was more improvement (62–52%). In the reference population, the highest prevalence of major LARS‐like symptoms was noted in older women (12%). Preoperative radiotherapy, defunctioning stoma and tumour height were found to be associated with major LARS. Conclusion: Major LARS is common and possibly persistent over time. Younger patients, especially women, are more affected, and perhaps these patients should be prioritized for early stoma closure to improve the chance of a more normal bowel function.